2020
DOI: 10.3762/bjnano.11.129
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial metal-based nanoparticles: a review on their synthesis, types and antimicrobial action

Abstract: The investigation of novel nanoparticles with antimicrobial activity has grown in recent years due to the increased incidence of nosocomial infections occurring during hospitalization and food poisoning derived from foodborne pathogens. Antimicrobial agents are necessary in various fields in which biological contamination occurs. For example, in food packaging they are used to control food contamination by microbes, in the medical field the microbial agents are important for reducing the risk of contamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 169 publications
(183 reference statements)
0
38
0
Order By: Relevance
“…Third, the study of fabrication and new materials of micro/nanorobots. With the continuous development of nanotechnology, more and more new materials and new technologies have emerged [51,52]. In order to make good use of micro/nanorobots in biomedicine and other fields, new fabrication methods of micro/ nanorobots should be explored, and more biocompatible nanomaterials should be selected to reduce costs and expand applications.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the study of fabrication and new materials of micro/nanorobots. With the continuous development of nanotechnology, more and more new materials and new technologies have emerged [51,52]. In order to make good use of micro/nanorobots in biomedicine and other fields, new fabrication methods of micro/ nanorobots should be explored, and more biocompatible nanomaterials should be selected to reduce costs and expand applications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the membrane damage by antimicrobial agents must occur through different mechanisms. It was observed that metal NPs (usually with positive charges) are more active against Gram-positive bacteria, having higher permeability and negative charges on the surface, that attract NPs, in comparison with Gram-negative bacteria, where the double membrane, with a lower negative charge, acts as a physical barrier against hydrophobic compounds [ 14 ].…”
Section: Enhancement Of Antimicrobial Properties Via Nanomodification Of Epoxiesmentioning
confidence: 99%
“…(a) Nanocomposites. Since ancient times, materials containing silver or copper have been used as antimicrobial agents; nowadays metallic (i.e., Ag and Cu) and metal-oxide (i.e., ZnO, CuO, NiO, TiO 2 ) nanoparticles provide strong antimicrobial activity in small dosages against a wide variety of microorganisms due to their dimensions, shapes, charges, high ratio of surface areas to mass, and high reactivities [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Due to electronic, optical, and magnetic properties, multi-metallic nanoparticles were recently proposed as innovative antimicrobial agents, which could help to overcome antimicrobial resistance [ 32 ].…”
Section: Enhancement Of Antimicrobial Properties Via Nanomodification Of Epoxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of a top‐down approach from bulk metal, one can name high‐intensity ultrasound treatment, [8] the spark erosion method [9] or the surfactant‐assisted solution plasma technique [10] . The ablation method, the next top‐down method for the preparation of metallic nanoparticles, [11] was used for the Ge−Sn alloy or SnO x nanoparticles [12] . The tin nanoparticles resulting from the procedures mentioned above are nearly spherical but with a large size distribution (e. g. 50–3500 nm [8] ).…”
Section: Introductionmentioning
confidence: 99%